USING SHADOWING TECHNIQUE IN TEACHING SPEAKING TO THE ELEVENTH GRADE STUDENTS OF MAS DARUL FATH BONTOLANGKASA - Misrawati; Anugrawati, Nunung; Mallapiang, Yassir (FKIP Unismuh Makassar, 2023)
The objective of this research was to find out the students’ speaking skill by using shadowing technique at the Eleventh Grade of MAS Darul Fath Bontolangkasa The researcher used a pre-experimental research is included in the Quantitative method. Quantitative method is a method of collecting and analysing data from various sources in an organized manner. Quantitative method which emphasized on Shadowing Technique application as treatment and it’s impact on student speaking skill. Purposive sampling technique to be used in this research. It consisted 1 class of the students, the number of population was 7 students.The sample of this research was class XI in which the number of the sample was 7 students. The instrument of this research was used speaking test. In collecting the data the researcher used test namely speaking test which was distributed in pre-test and post-test and used the research instrument was speaking test. Based on the findings, it was found that students were could be taught to speaking and indicated that achievement of the Eleventh Grade of MAS Darul Fath Bontolangkasa was improved by using shadowing technique .This was evidenced by the mean score in terms of content pre-test was 61 and post-test was 80the improvement of the content was 0.32 % which means there was significant difference between pre-test and post-test. Based on the research finding the researcher concluded that using shadowing technique in teaching English for students’ proven improved their speaking skill.